Phytochemical Analysis of Medicinal Plants Used in the Treatment of Malaria Infection in Billiri and Funakaye Local Government Areas of Gombe State - Daniel J. L.; Vandi P; Chessed, G.; Umar, M.; Yusuf, A. I., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The survey research was carried out to identify the plants used in the treatment of malaria fever in Funakaye and Billiri Local Government Areas of Gombe state, Nigeria. Traditional healers and elderly people of these areas were visited and interviewed on medicinal plants used by them. A semi structured questionnaire and open ended conversation was employed. The interview and discussions was conducted in Hausa language being a common language used by the people in the study areas. Several trips was made to the sites where they usually go to harvest the plants. Data on the common names of the plants and parts used was recorded on the field. Plants names were identified using a field key to the Savannah trees of Nigeria. A total of nine (9) plants were identified based on the usage, availability and acceptability in these wards. Carica papaya (Paw paw/Gwanda) and Khaya grandifoliola (Mahogany/Madachi) was common to the locals in Billiri Local government area, while the other plants are common in both local governments areas. All plant samples were air dried at room temperature for three weeks after which, they were taken to an electric grinding machine where the engine was properly washed and dried to avoid contamination. The plant samples were grounded to the required texture. Phytochemical analysis using aqueous and ethanol extractions revealed the presence of tannins, alkaloids, saponins glycosides, terpenoids, flavonoids, steroids and phenols in various quantity. These medicinal plants are common and qualitative analysis showed that they contained properties which has antimicrobial effects.